2012
DOI: 10.1097/mca.0b013e3283564986
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between red blood cell distribution width and the clinical outcomes in non-ST elevation myocardial infarction and unstable angina pectoris

Abstract: RDW is a readily available clinical laboratory value associated with long-term cardiovascular mortality in NSTEMI and UAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 27 publications
6
47
0
1
Order By: Relevance
“…In a prospective study, Gul et al [15] showed that high RDW levels were associated with long-term cardiovascular mortality in patients with non-STEMI and unstable angina pectoris. Van Kimmenade et al [16] demonstrated that high RDW level was an independent indicator of 1-year mortality in acute cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, Gul et al [15] showed that high RDW levels were associated with long-term cardiovascular mortality in patients with non-STEMI and unstable angina pectoris. Van Kimmenade et al [16] demonstrated that high RDW level was an independent indicator of 1-year mortality in acute cardiac failure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a relationship between high RDW and increased mortality and morbidity in short term follow up of patients with acute and chronic heart failure (15,16) . A study by Gul et al reported that RDW was related to long-term mortality in patients with acute coronary syndrome (17) . In a study by Uyarel et al, high RDW was shown to be related with in-hospital and long-term increased cardiovascular mortality in 2506 patients with ST segment elevated myocardial infarction that underwent primary angioplasty (2) .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of easy measurement and evaluation of biochemical and hematological parameters in patients with acute coronary syndromes had been shown in previous studies [6][7][8].…”
mentioning
confidence: 97%